Parental behavior, cognitive appraisal, and motivation in young athletes - Gomes, A.; Gonçalves, A.; Dias, O.; Morais, C. (Research Quarterly for Exercise and Sport, 2019)
Purpose: This study tested two hypotheses relating young athletes' sports motivations to parental behaviors and cognitive appraisal: (1) young athletes' motivation in sports is related to their parents' behavior; and (2) this relationship is mediated by cognitive appraisal, even after controlling for competitive level and sports records. Method: This cross-sectional study included 673 young athletes and it measured the athletes' perceptions of parental behaviors, cognitive appraisal, and sports motivation. Results: Structural equation modeling confirmed Hypothesis 1-the mother's behaviors accounted for 15 to 16% of the variance in sports motivation, and the father's behaviors accounted for 12 to 21% of the variance. The correlation patterns differed according to whether the athletes were evaluating the mother's or father's behaviors. Hypothesis 2 also was confirmed, for cognitive appraisal partially mediated the relationship between the perception of parental behaviors and sports motivation (34% of the variance was accounted for by the perception of the mother's behavior; 30% by the father's). The mediating model did not vary with competitive level or sports records. Conclusion: Parental behaviors and cognitive appraisal need to be taken into account to understand young athletes' sports motivations.